Ethics Literacy and “Ethics University”: Two Intertwined Models for Public Involvement and Empowerment in Bioethics - Strech, Daniel; Hirschberg, Irene; Meyer, Antje; Baum, Annika; Hainz, Tobias; Neitzke, Gerald; Seidel, Gabriele; Dierks, Marie-Luise (Frontiers in Public Health, 2016)
Background: Informing lay citizens about complex health-related issues and their related ethical, legal and social aspects (ELSA) is one important component of democratic health care/research governance. Public information activities may be especially valuable when they are used in multi-staged processes that also include elements of information and deliberation. Objectives: This paper presents a new model for a public involvement activity on ELSA (ethics university) and evaluation data for a pilot event. Methods: The ethics university is structurally based on the ‘patient university’, an already established institution in some German medical schools, and the newly developed concept of ‘ethics literacy’. The concept of ‘ethics literacy’ consists of three levels: information, interaction, and reflection. The pilot project consisted of two series of events (lasting four days each). Results: The thematic focus of the ethics university pilot was ELSA of regenerative medicine. In this pilot the concept of ‘ethics literacy’ could be validated as its components were clearly visible in discussions with participants at the end of the event. The participants reacted favorably to the ethics university by stating that they felt more educated with regard to the ELSA of regenerative medicine and with regard to their own abilities in normative reasoning on this topic. Conclusion: The ethics university is an innovative model for public involvement and empowerment activities on ELSA theoretically underpinned by a concept for ‘ethics literacy’. This model deserves further refinement, testing in other ELSA topics and evaluation in outcome research .